Spatio-temporal dynamics and aetiology of proliferative leg skin lesions in wild British finches. Issue 1 (December 2018) - Lawson, Becki; Robinson, Robert; Fernandez, Julia; John, Shinto; Benitez, Laura; Tolf, Conny; Risely, Kate; Toms, Mike; Cunningham, Andrew; Williams, Richard
Abstract Proliferative leg skin lesions have been described in wild finches in Europe although there have been no large-scale studies of their aetiology or epizootiology to date. Firstly, disease surveillance, utilising public reporting of observations of live wild finches was conducted in Great Britain (GB) and showed proliferative leg skin lesions in chaffinches (Fringilla coelebs ) to be widespread. Seasonal variation was observed, with a peak during the winter months. Secondly, pathological investigations were performed on a sample of 39 chaffinches, four bullfinches (Pyrrhula pyrrhula ), one greenfinch (Chloris chloris ) and one goldfinch (Carduelis carduelis ) with proliferative leg skin lesions and detectedCnemidocoptes sp. mites in 91% (41/45) of affected finches and from all species examined.Fringilla coelebs papillomavirus (FcPV1) PCR was positive in 74% (23/31) of birds tested: a 394 base pair sequence was derived from 20 of these birds, from all examined species, with 100% identity to reference genomes. Both mites and FcPV1 DNA were detected in 71% (20/28) of birds tested for both pathogens. Histopathological examination of lesions did not discriminate the relative importance of mite or FcPV1 infection as their cause. Development of techniques to localise FcPV1 within lesions is required to elucidate the pathological significance of FcPV1 DNA detection.